2370. Dalbavancin Use in Emergency Department and Observation Unit to Prevent Inpatient Admission for Acute Bacterial Skin and Skin Structure Infection (ABSSI). (26th November 2018) - Ford, Jonathan; Lee, Jean
Abstract: Background: ABSSSIs are a common cause of hospitalization. Dalbavancin (DBV) is a lipoglycopeptide antibiotic approved as a single 1, 500 mg intravenous (IV) dose for the treatment of patients with ABSSSI. DBV offers a unique opportunity for cost avoidance by shifting more ABSSI treatment to the outpatient setting. In late 2016, DBV was added to Northwest Hospital formulary with a restriction to patients with ABSSSI in the emergency department (ED) and observation unit who would otherwise be admitted for IV antibiotic therapy. The objective of this study was to assess the resource-effectiveness of DBV infusion as an alternative to inpatient admission for ABSSI management. Methods: We performed a retrospective review of patients that received DBV in calendar-year (CY) 2017. The primary outcome was avoidance of inpatient admission and 30-day return to any ED as captured by the Chesapeake Regional Information System. Secondary outcomes were reported adverse drug reactions (ADRs) and inpatient resource utilization for the diagnosis-related group of cellulitis without major complication or comorbidity (MS-DRG 603) in CY 2017 vs. CY 2016. Results: A total of 32 patients received DBV in 2017 in the ED or observation setting. Of these, one was admitted the same day and seven had ED returns within 30 days. Of these seven patients, only two had ED returns related to ongoing cellulitis/possible DBV failure. One of these two patients received a second dose of DBV and was sent home while the other required inpatient admission. There were no DBV ADRs noted. Regarding inpatient resource utilization, 121 patients were admitted for MS-DRG 603 in 2017 vs. 167 patients in 2016, average length of stay was 3.88 days in 2017 vs 3.92 days in 2016, and average cost per inpatient stay was $4, 076 in 2017 vs.. $6, 314 in 2016. The total hospital cost for MS-DRG 603 was $555, 000 in 2017 vs. $1 million in 2016. Conclusion: A single dalbavancin infusion is a resource-effective option for patients with ABSSSI that would otherwise require inpatient admission for IV antibiotics. Disclosures: All authors: No reported disclosures.